Crescimento e trocas gasosas em mudas de Mauritia flexuosa em respostas à disponibilidade hídrica - Tarcísia da Silva Almeida (2018)
The buritizeiro (Mauritia flexuosa L.) is a tree palm distributed in South America, and in Brazil it is present in the state of Amazonia and in regions of Cerrado with occurrence of areas of veredas with predominance of organosol. These areas undergo anthropic and environmental actions, interfering in water availability, inducing species degradation and extinction. Thus, the objective of this work is to evaluate the morphometric and physiological changes in buritizeiro seedlings grown in organsoil with different water contents. The experiment was a randomized block design with five treatments (100, 80, 60, 40 and 0% of available water), four replications, five pots per replicate and one seedling per pot. Soil and seeds from the Vereda located in the area of environmental protection of the Rio Pandeiros, in the municipality of Bonito de Minas-MG. The daily weighing of the pots was performed using a mechanical scale and the humidity adjusted according to the applied treatment. The mortality of the plants, diameter in the collecting region, height of the plant, emission of leaves, number of open leaves, root and shoot dry matter, stomatal conductance, assimilated carbon, transpiration and water use efficiency were evaluated. During the experiment, 10% of the plants died in the 0% water availability treatment. The plants with greater availability of water presented larger diameter. The length of the eophile, first and second leaf, of the plants with 80 and 100% of available water showed greater development in relation to plants with less water, this same characteristic was observed for the percentage of eophile, first and second open leaf. In the group of plants with the third, fourth and fifth leaf emitted, treatments with high availability of water induce a greater number of leaves. In the physiological analysis, the plants showed an increasing linear response, except for the variable corresponding to the efficient use of water in which there was no difference. The dry matter data were similar to the other variables. Plants that were submitted to higher percentages of water availability developed more efficiently. Therefore, the buritizeiro presented resistance to water deficit, since it was possible to observe that even under conditions of low water availability the plants survived, but with a compromised vegetative development.